Smooth muscle αv integrins regulate vascular fibrosis via CD109 downregulation of TGF-β signalling. Issue 2 (16th February 2023) - Li, Zhenlin; Belozertseva, Ekaterina; Parlakian, Ara; Bascetin, Rümeyza; Louis, Huguette; Kawamura, Yuki; Blanc, Jocelyne; Gao-Li, Jacqueline; Pinet, Florence; Lacy-Hulbert, Adam; Challande, Pascal; Humphrey, Jay D; et al.
Abstract: Aims: αv integrins are implicated in fibrosis in a number of organs through their ability to activate TGF-β. However their role in vascular fibrosis and collagen accumulation is only partially understood. Here we have used αv conditional knockout mice and cell lines to determine how αv contributes to vascular smooth muscle cell (VSMC) function in vascular fibrosis and the role of TGF-β in that process. Methods and results: Angiotensin II (Ang II) treatment causes upregulation of αv and β3 expression in the vessel wall, associated with increased collagen deposition. We found that deletion of αv integrin subunit from VSMCs (αv SMKO ) protected mice against angiotensin II-induced collagen production and assembly. Transcriptomic analysis of the vessel wall in αv SMKO mice and controls identified a significant reduction in expression of fibrosis and related genes in αv SMKO mice. In contrast, αv SMKO mice showed prolonged expression of CD109, which is known to affect TGF-β signalling. Using cultured mouse and human VSMCs, we showed that overexpression of CD109 phenocopied knockdown of αv integrin, attenuating collagen expression, TGF-β activation, and Smad2/3 signalling in response to angiotensin II or TGF-β stimulation. CD109 and TGF-β receptor were internalized in early endosomes. Conclusion: We identify a role for VSMC αv integrin in vascular fibrosis and show that αv acts in concert with CD109 to regulate TGF-β signalling. Graphical Abstract: Graphical abstract